Energetic instability of passive states in thermodynamics - Carlo Sparaciari (Nature Portfolio, 2017)
Is it possible to single out the thermal state from all the passive states even when not operating in the thermodynamic limit? Here, the authors show that an optimal amount of energy can be extracted from any athermal quantum state when using a machine that operates in a reversible cycle.